Economy-Wide Impact of Electricity Price Increases in Bangladesh : A CGE Analysis - Timilsna, Govinda; Pargal, Sheoli; Tsigas, Marinos; Sahin, Sebnem (World Bank, Washington, DC, 2018)
This paper presents an analysis of the economic impact of electricity price increases in Bangladesh. A computable general equilibrium (CGE) model is developed and used to trace through the impact of an increase in the price of electricity on GDP, household consumption, economy-wide investment, government income, the trade balance, inflation, and sectoral outputs and prices. The primary motivation for this analysis is the need to understand the impact of adjusting the price of electricity to reduce the significant fiscal burden of current budget transfers to the single buyer of wholesale power – de facto subsidies to the end-consumer. Another impetus is the fact that the impending import of liquefied natural gas (LNG) will result in a more expensive fuel mix for power generation, which will lead to a need to increase the price of electricity supplied to consumers. Both channels impacting the price of electricity are modeled and their impacts analyzed. The model takes into account the fact that a reduction in subsidies to the sector or an increase in the price of electricity will augment government revenues, which can be recycled towards productive ends. The value of the model lies in the indicative results, insights and options it provides for decision-makers to take into account in their planning andpolicy formulation. Going forward, it would be important to carry out a supplementary distributional analysis to understand the implications for the poor and thus the full potential impact of the policy changes being analyzed.